What Makes an Instrument Sound Sad? Commentary on Huron, Anderson, and Shanahan - Vuoskoski, Jonna K. (Empirical Musicology Review, 2014)
Huron, Anderson, and Shanahan investigated the hypothesis that instruments that are deemed most capable of expressing sadness would also be judged better able to generate acoustic features similar to those used to convey sadness in speech. The judgments of these acoustic features accounted for approximately half (51.3%) of the variance in the judgments of sadness capacity. I argue that the relatively low explanation rate may be partly explained by choices made in the operationalization of the acoustic features, the overlap and relatedness of three of the acoustic features used (mumbling, dark timbre, and lowest pitch), as well as the practical omission of such a significant feature as legato articulation. Furthermore, the method used by Huron and colleagues may have inflated the effect of cultural conceptions on the judgments of sadness capacity. I also argue that low energy – albeit a fundamental feature of sadness as an emotion – is not the meaningful factor underlying the set of acoustic features most correlated with sadness capacity. Instead, I suggest that the only acoustic variable significantly predicting evaluations of sadness capacity – pitch-bending – best reflected an instrument’s capability to manipulate timbre, pitch, loudness and articulation in ways that match and exaggerate the features of sad vocal expression.